Ponding of Two-Way Roof Systems - Marino, Frank J. (Engineering Journal, 1966)
Several papers have been published analyzing roof beams subject to ponding. However, the scope of these papers has been limited to the one-directional action of beams. That is, the flexural members are considered supported by unyielding knife edges with no consideration given to surface deflection transverse to the beam span under study. The effect of interaction between members in a roof framing system can be considerable and should not be neglected. The present AISC Specification is cognizant of the ponding problem. Chinn points out that the Specification provision is arbitrary in nature and could be overly conservative. It is interesting to note here that in all the cases of collapse attributed to the ponding phenomenon that the author has reviewed, the members involved did violate the present Specification provision. However, the provision may actually be unconservative for very large spans. The purpose of this paper is to analyze the ponding of a roof system, accounting for the interaction of members and to develop a design aid suitable for office use. A restriction imposed on the analysis is that the structural system must consist essentially of two-way framing (i.e., main girders or primary members and secondary sub-members spanning perpendicular to the girders) with the deck contributing negligible deflection to the system. However, if in the absence of other sub-members the deck spans a substantial distance between main members, it should be treated as the secondary system.